Pelaksanaan Bina Iman Anak (BIA) Dalam Mengembangkan Iman Anak Di Sekolah Dasar Katolik Sang Timur Malang - Pedro Lopes; Fransisko Amadino Heli; Yohanes Wilson Bei Lena Mao (Jurnal Pelayanan Pastoral, 2024)
Children's Faith Education (BIA) at Sang Timur Catholic Elementary School in Malang plays an important role in developing children's faith. This study aims to determine the purpose of BIA, the methods and materials used, the role of BIA teachers, the obstacles and solutions in the implementation of BIA, and the impact of BIA on children's faith development. This research uses a qualitative method with a descriptive approach. Data were obtained through observation, interviews, and documentation. The results showed that BIA at Sang Timur Catholic Elementary School in Malang aims to help children recognize, understand, and live the Catholic faith. The methods used vary, such as lectures, discussions, playing, and singing. BIA materials are adapted to the age and developmental level of children, including Bible stories, prayers, sacraments, morals, and liturgy. BIA teachers have an important role in developing children's faith by being role models and delivering materials in an interesting way. The obstacles in implementing BIA are lack of time and resources. The solution offered is to increase cooperation between schools, parents and churches. The impact of BIA on children's faith development is positive, namely children become more familiar with God, understand the Catholic faith, and live it in their daily lives.